Antimicrobial Resistance among Clinical Isolates of Streptococcus pneumoniae in the United States during 1999–2000, Including a Comparison of Resistance Rates since 1994–1995 - Doern, Gary V. (American Society for Microbiology, 2001)
A total of 1,531 recent clinical isolates of Streptococcus pneumoniae were collected from 33 medical centers nationwide during the winter of 1999–2000 and characterized at a central laboratory. Of these isolates, 34.2% were penicillin nonsusceptible (MIC ≥ 0.12 μg/ml) and 21.5% were high-level resistant (MIC ≥ 2 μg/ml). MICs to all beta-lactam antimicrobials increased as penicillin MICs increased. Resistance rates among non-beta-lactam agents were the following: macrolides, 25.2 to 25.7%; clindamycin, 8.9%; tetracycline, 16.3%; chloramphenicol, 8.3%; and trimethoprim-sulfamethoxazole (TMP-SMX), 30.3%. Resistance to non-beta-lactam agents was higher among penicillin-resistant strains than penicillin-susceptible strains; 22.4% of S. pneumoniae were multiresistant. Resistance to vancomycin and quinupristin-dalfopristin was not detected. Resistance to rifampin was 0.1%. Testing of seven fluoroquinolones resulted in the following rank order of in vitro activity: gemifloxacin > sitafloxacin > moxifloxacin > gatifloxacin > levofloxacin = ciprofloxacin > ofloxacin. For 1.4% of strains, ciprofloxacin MICs were ≥4 μg/ml. The MIC(90)s (MICs at which 90% of isolates were inhibited) of two ketolides were 0.06 μg/ml (ABT773) and 0.12 μg/ml (telithromycin). The MIC(90) of linezolid was 2 μg/ml. Overall, antimicrobial resistance was highest among middle ear fluid and sinus isolates of S. pneumoniae; lowest resistance rates were noted with isolates from cerebrospinal fluid and blood. Resistant isolates were most often recovered from children 0 to 5 years of age and from patients in the southeastern United States. This study represents a continuation of two previous national studies, one in 1994–1995 and the other in 1997–1998. Resistance rates with S. pneumoniae have increased markedly in the United States during the past 5 years. Increases in resistance from 1994–1995 to 1999–2000 for selected antimicrobial agents were as follows: penicillin, 10.6%; erythromycin, 16.1%; tetracycline, 9.0%; TMP-SMX, 9.1%; and chloramphenicol, 4.0%, the increase in multiresistance was 13.3%. Despite awareness and prevention efforts, antimicrobial resistance with S. pneumoniae continues to increase in the United States.